1980
DOI: 10.1093/carcin/1.8.685
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic, transforming and promoting effect of pickled vegetables from Linxian county, China

Abstract: A recent epidemiological survey in China showed that there is a regional distribution of esophageal cancer and a correlation between mortality for this cancer and environmental factors, especially the consumption of pickled vegetables. A series of experimental studies with pickled vegetable extract were done using different in vitro biological systems. The results showed that pickled vegetable extract induced 6-thioguanine-resistant mutants in V79 cells and increased sister chromatid exchanges in the same cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…We found that the processed vegetables were positively associated with gastric cancer, even after considering other potential confounders. In addition to high salt in the processed vegetables, it was reported that heavy contamination with fungi might exist as well during reparation and preservation, particularly during preparing preserved vegetable (Cheng et al, 1980). Although some common fungi can reduce nitrate to nitrite, they also increase amines content of pickled vegetables (Li et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the processed vegetables were positively associated with gastric cancer, even after considering other potential confounders. In addition to high salt in the processed vegetables, it was reported that heavy contamination with fungi might exist as well during reparation and preservation, particularly during preparing preserved vegetable (Cheng et al, 1980). Although some common fungi can reduce nitrate to nitrite, they also increase amines content of pickled vegetables (Li et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…This can facilitate the endogenous formation of N-nitroso compounds, which have been proven to be strong carcinogenic to several sites of cancer (Scanlan, 1983). Extracts of pickled vegetables from one of the high risk areas in China have shown mutagenic and transforming potency in vitro (Cheng et al, 1980). Furthermore, a synergistic interaction between moldy food and N-nitroso compounds has been reported (Cheng et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The traditional way of preparing pickled vegetables, packing moist vegetables in a jar for a few weeks or months, allows fermentation and growth of fungi and yeasts (5,7) and can potentially yield carcinogenic compounds such as N-nitroso compounds and mycotoxins (5,8,9). Indeed, a number of experimental and in vitro studies have shown mutagenicity and carcinogenicity of pickled vegetables (5,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenicity and carcinogenicity of pickled vegetables have been shown in some experimental and in vitro studies (Cheng et al, 1980;Yang, 1980;Lu et al, 1981).…”
mentioning
confidence: 96%